Slow alignment of GMO allergenicity regulations with science on protein digestibility. Issue 1 (31st December 2022) - Herman, Rod A.; Zhang, John X. Q.; Roper, Jason M.
ABSTRACT: The current science on food allergy supports the dual allergen exposure hypothesis where sensitization to allergenic proteins is favored by dermal and inhalation exposure, and tolerization against allergy is favored by exposure in the gut. This hypothesis is bolstered by the epidemiological evidence showing that regions where children are exposed early in life to allergenic foods have lower rates of allergy. This led medical experts to replace the previous recommendation to exclude commonly allergenic foods from the diets of young children with the current recommendation that such foods be introduced to children early in life. Past beliefs that lowering gut exposure would reduce the likelihood that a protein would be allergenic led regulators and risk assessors to consider digestively stable proteins to be of greater allergenic risk. This resulted in international guidance and government regulations for newly expressed proteins in genetically engineered crops that aligned with this belief. Despite empirical results showing that allergens are no more digestively stable than non-allergens, and that gut exposure favors tolerization over sensitization, regulations have not come into alignment with the current science prompting developers to continue to engineer proteins for increased digestibility. In some rare cases, this could potentially increase sensitization risk.